Dead in bed – A systematic review of overnight deaths in type 1 diabetes. (September 2022) - Jones, Jessica; James, Steven; Brown, Fran; O'Neal, David; I Ekinci, Elif
Highlights: Dead in bed syndrome is a leading cause of overnight mortality. There is a lack of recent data about overnight type 1 diabetes mortality. There is a paucity of information about technology and impact on overnight mortality. Abstract: Background: Type 1 diabetes is a significant, life-long condition which affects many people worldwide. One of the most feared causes of type 1 diabetes mortality, overnight mortality, often caused by the dead in bed syndrome, is largely underreported. A systematic literature search was undertaken to understand the frequency, risk factors, causes and impact that diabetes-related technologies have on overnight mortality, in this population. Methods: MEDLINE (Ovid), Embase (Ovid) and Cochrane were searched to June 2021, using defined inclusion and exclusion criteria. Quality appraisal was undertaken. Results: Overall, 26 records met the inclusion criteria. Large-scale cohort studies examined data up to 2013, and there were no studies published after 2018. The proportion of deaths attributable to the dead in bed syndrome was between 2 and 5% of deaths in children, adolescents, and young adults, with a slight decrease in proportion of dead in bed syndrome since 1991. Conclusion: Overnight mortality is occurring for people with type 1 diabetes, reported as recently as in 2018. Living alone, alcohol and illicit substances consistently appear as risk factors, and the impact of technology on overnight mortality is not fully understood, with more recent data, from larger cohort studies being required.